Optical properties and crystallinity of hydrogenated nanocrystalline silicon (nc-Si:H) thin films deposited by rf-PECVD - Tong, G.B.; Aspanut, Z.; Muhamad, M.R.; Rahman, S.A. (2012)
Hydrogenated nanocrystalline silicon (nc-Si:H) thin films prepared in a home-built radio-frequency (rf) plasma enhanced chemical vapour deposition (PECVD) system have been studied. The rf powers were fixed in the range of 5 W-80 W. The optical properties and crystallinity of the films were studied by X-ray diffraction (XRD), Micro-Raman scattering spectroscopy, high resolution transmission electron microscope (HRTEM), and optical transmission and reflection spectroscopy. The XRD and Micro-Raman scattering spectra were used to investigate the evidence of crystallinity in order to determine the crystallite sizes and crystalline volume fraction in the films. The HRTEM image of the film was used to correlate with the crystallinity that was determined from XRD and Micro-Raman scattering spectra. Optical constants such as refractive index, optical energy gap, Tauc slope, Urbach energy and ionic constants were obtained from the optical transmission and reflectance spectra. From the results, it was interesting to found that the optical constants showed a good correlation with the crystallinity within the variation of rf power. Also, the ionic constants of the films showed an indication of the degree of crystallinity in the films. The variation of the optical energy gap with the rf power based on structure disorder and the quantum confinement effect is discussed. (C) 2011 Elsevier Ltd. All rights reserved.